Dissolved organic matter characteristics and removal of trace organic contaminants in a multi-soil-layering system. Issue 4 (August 2021) - Maeng, Sung Kyu; Park, Ji Won; Noh, Jin Hyung; Won, Se-Yeon; Song, Kyung Guen
Abstract: This study investigated the role of soil mixture blocks (SMBs) in the removal of trace organic contaminants and the changes in dissolved organic matter characteristics in a laboratory-scale multi-soil-layering (MSL) system. The experimental setup included three soil-based water treatment systems, namely MSL, MSL without SMBs (zeolite/slag), and a sand filter. The effect of SMBs in the removal of dissolved organic matter in MSL was not significant, but the use of zeolite/slag in MSL enhanced the removal of humic substances and building blocks. Through membrane fractionation, the size distribution of dissolved organic matter in the MSL system was not changed, and the majority of the dissolved organic matter is below 1 kDa. Ten pharmaceutically active compounds and three endocrine-disrupting compounds were used to investigate the removal of selected trace organic contaminants in the MSL system, zeolite/slag, and sand filter. The attenuation of pentoxifylline, caffeine, 17α-ethinylestradiol, estrone, and 17β-estradiol in the MSL system was similar to that for zeolite/slag, and the removal efficiency was greater than 80%. However, pentoxifylline, caffeine, 17α-ethinylestradiol, estrone, and 17β-estradiol exhibited relatively low removal efficiencies in the sand filter compared to those in the MSL system and zeolite/slag. Results from this study provide insight into the removal of selected trace organic contaminants in MSL system, which could be considered as one of the series of barriers to remove trace organic contaminants in wastewater. Graphical Abstract: ga1 Highlights: The use of zeolite/slag in MSL enhanced the removal of humics. The attenuation of E2, E1, EE2, caffeine, and pentoxifylline was effective in MSL. Soil mixture block was not significant in the removal of trace organic contaminants.